Perilaku Pemustaka Dalam Temu Kembali Koleksi Dengan Menggunakan OPAC Berbasis SLIMS - Mujiati Mujiati (IAIN Ponorogo, 2014)
Abstract: An increase of library collection and information explosion causes problems on information retrieval for library users. Those explosion will be helpful for users using Online Public Access Catalog (OPAC). This article tries to explore the use of OPAC based SLIMs on STAIN Ponorogo library. OPAC proves to help users on retrieval be easier and faster, beside its obstacles